ANALISA PERBANDINGAN UNJUK KERJA PEMAKAIAN BAHAN BAKAR MOTOR KONVENSIONAL DENGAN MOTOR LISTRIK ULC PLN AREA CENGKARENG - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
The depletion of petroleum reserves makes people always try to find alternative energy to meet their daily needs. Especially for fuel oil in vehicles whose price is increasing, making scientists to look for alternative energy as a vehicle. Electric motors are one of the alternatives currently being promoted to replace oil-fueled vehicles. There are many types and models of electric motors in the community. The research that will be done is to test the performance of electric motorcycle used by PLN Cengkareng Area for the activities of Quick Service Unit (ULC = Unit Layanan Cepat) and compared with conventional motorcycle fueled by premium oil